"Deep" Learning and Computer Mediated Communication: A case study of on-line teacher education - Motteram, Gary; Teague, Joanna (Proceedings of the International Conference on Networked Learning, 2000)
In the Centre for English Language Studies at The University of Manchester we run a Master's degree in Educational Technology and English Language Teaching (ELT) which is offered both in distance plus residential (a summer school), or full)' distance modes. As part of the programme participants take one module that is run fully on-line. Other modules make use of more traditional distance learning technologies, with on-line support via email. The module in question is called 'Computers and Video as a Resource' (CVR) and is usually taken as the last of six taught components. The reasons for delivering this module on-line are: Course participants experience different kinds of computer mediated communication (CmC) as an integral pan of their distance learning rather than just reading about them. Participants can then reflect on their use of CmC and consider how they might be used in their own professional context. We look at issues such as teacher education, testing, research and management.